The chain & sum primitive and its applications to MACs and stream ciphers - Jakubowski, Mariusz; Venkatesan, Ramarathnam (Advances in Cryptology - Eurocrypt '98, 1998)
We present a new scheme called universal block chaining with sum (or chain & sum primitive (C&S) for short), and show its application to the problem of combine encryption and authentication of data.